Pertanggungjawaban Pidana terhadap Influencer yang Melakukan Promosi Situs Judi Online saat Live Streaming di Media Sosial - Ibnu Abdul (CV Rewang Rencang, 2025)
This research examines criminal liability of influencers who promote online gambling sites through live streaming on social media. The research method is normative juridical with statutory and case study approaches. Findings show influencers can be held criminally liable under Article 27 paragraph (2) in conjunction with Article 45 paragraph (2) of ITE Law and Article 303 in conjunction with Article 303 bis of Criminal Code if elements of actus reus and mens rea are fulfilled. Law enforcement is carried out through preventive approaches such as education and supervision, and repressive measures through judicial processes. Obstacles include substantive, structural, cultural, and technical aspects requiring regulatory strengthening and multi-stakeholder cooperation